2019
DOI: 10.22159/ajpcr.2019.v12i9.33378
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Prescribing Pattern in Geriatric Patients

Abstract: Objective: The objective of this study was to study the prescribing pattern in geriatric patients. Methods: A prospective study was carried out for a period of 4 years with one of the objectives to study the prescribing pattern in geriatric patients (≥65 years). The information was collected, from patients admitted to various departments of tertiary care hospital and old-age home at Chitradurga. Sociodemographic, economic, and clinical diagnosis and medication details were collected from medical records… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…Maximum drugs prescribed were from respiratory system (21.1%), followed by GIT (19%), antimicrobials (14.9%), cardiovascular (11.8%), NSAIDs (10.8%), and vitamins (8.1%). Almost similar trend of prescribing has been reported in the past in Indian set up [8,14,16]. However, study from developed country showed cardiovascular drugs, diuretics, and psychotropic drugs accounted for 64% of all drug prescriptions, but these results pertained in population comprised 75 years or above [17].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Maximum drugs prescribed were from respiratory system (21.1%), followed by GIT (19%), antimicrobials (14.9%), cardiovascular (11.8%), NSAIDs (10.8%), and vitamins (8.1%). Almost similar trend of prescribing has been reported in the past in Indian set up [8,14,16]. However, study from developed country showed cardiovascular drugs, diuretics, and psychotropic drugs accounted for 64% of all drug prescriptions, but these results pertained in population comprised 75 years or above [17].…”
Section: Discussionsupporting
confidence: 64%
“…About 38.5% of total prescriptions had drugs more than 5 drugs, while 61% had five or less number of drugs. About 56.2% of geriatric are reported to receive six or more medication (polymedication) in one study [14].…”
Section: Discussionmentioning
confidence: 99%
“…In elderly with renal and hepatic dysfunction, FDCs may lead to unnecessary and prolonged exposure to drugs and increase risk of drug toxicity [12]. Drugs acting on alimentary tract (22.1%), followed by anti-microbial agents (18.4%), respiratory system (14.7%), and cardiovascular system (9.8%) were the most were commonly prescribed class of drugs, which was comparable to a study done by Nataraj and Bharathi in South India [16]. Overall, 60.5% of the total drugs prescribed were from the NLEMs 2015.…”
Section: Discussionsupporting
confidence: 58%